Assessment of salivary calcium, phosphate, magnesium, pH, and flow rate in healthy subjects, periodontitis, and dental caries - Rajesh, K. S. (Contemp Clin Dent, 2015)
AIM: This study was conducted to estimate and compare inorganic salivary calcium, phosphate, magnesium, salivary flow rate, and pH of unstimulated saliva and oral hygiene status of healthy subjects, subjects with periodontitis and dental caries, and to correlate salivary calcium level with number of intact teeth. MATERIALS AND METHODS: The study population consisted of 48 systemically healthy subjects in the age group of 18-55 years, which was further divided into three groups: healthy, periodontitis, and dental caries. Oral hygiene index-simplified, probing pocket depth, clinical attachment level, the number of intact teeth, and active carious lesions were recorded. Estimation of inorganic salivary calcium, phosphate, and magnesium was performed spectrophotometrically using Vitros 5.1 FS. Statistical analysis was performed using the one-way analysis of variance test at 5% significance level. RESULTS: There was a statistically significant increase in inorganic salivary calcium, phosphate, pH, flow rate, and poor oral hygiene status in periodontitis group compared to dental caries and healthy group. CONCLUSION: Subjects with increased inorganic salivary calcium, phosphate, pH, flow rate, and poor oral hygiene are at a higher risk of developing periodontitis. Since there is increased remineralization potential, these subjects have more number of intact teeth compared to the dental caries group.